Identification of leaf rust resistance genes in common wheat varieties from China and foreign countries - Yuan LIU; Takele Weldu GEBREWAHID; Pei-pei ZHANG; Zai-feng LI; Da-qun LIU (Journal of Integrative Agriculture, 2021)
Wheat leaf rust, triggered by Puccinia triticina Eriks (Pt), is among the most important diseases of wheat worldwide. Deploying resistant varieties against leaf rust is the most effective, environmentally-friendly and economic way to control the disease. In the present study, 66 wheat varieties form China and foreign countries were tested with 17 Pt races for gene postulation during the seedling stage in the greenhouse. All the varieties were also planted to identify slow rusting responses to leaf rust at the adult plant stage in Baoding and Zhoukou field trials during the 2016/2017 to 2017/2018 cropping seasons. Moreover, 12 closely linked molecular markers to known leaf rust resistance (Lr) genes were used for assessing all the varieties. The results of both gene postulation and molecular marker identification showed that a total of eight Lr genes, Lr1, Lr10, Lr17, Lr20, Lr26, Lr34, Lr37 and Lr46, either singly or in combination were detected in 32 varieties. Known Lr genes were not identified in the remaining 34 varieties. Seventeen varieties were found to have slow rusting resistance. The resistance sources identified in this study can be used as resources for resistance against leaf rust in wheat breeding programs in China and the respective foreign countries.